Answer :

It is given that,

The sum of the two numbers =

One of the number =

Suppose the other number is x

Since, the sum is

Therefore,

x - =

=

3x = 12 - 1

3x = 11

x =

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Verify the properRD Sharma - Mathematics

The sum of the twRD Sharma - Mathematics

The sum of two nuRD Sharma - Mathematics

Tell which properNCERT - Mathematics Exemplar

Find the multipliNCERT - Mathematics Exemplar

What number shoulRD Sharma - Mathematics